2007
DOI: 10.1002/ange.200603285
|View full text |Cite
|
Sign up to set email alerts
|

Acid Initiation of Ammonia–Borane Dehydrogenation for Hydrogen Storage

Abstract: Dabei kommt Wasserstoff heraus: Starke Lewis‐ oder Brønsted‐Säuren erzeugen in situ aus dem Ammoniak‐Boran‐Komplex (H3NBH3) ein Boroniumkation, das unter Freisetzung von H2 zu einer Mischung aus cyclischen und acyclischen BNHx‐Oligomeren reagiert (siehe Schema). Der vorgeschlagene Mechanismus wird durch Dichtefunktionalrechnungen zur Thermodynamik der Reaktion gestützt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
93
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 35 publications
4
93
0
4
Order By: Relevance
“…[3][4][5][6] The viability of any storage system is critically dependent on efficient recyclability, but reports on the latter subject are sparse.…”
mentioning
confidence: 99%
“…[3][4][5][6] The viability of any storage system is critically dependent on efficient recyclability, but reports on the latter subject are sparse.…”
mentioning
confidence: 99%
“…[1] In recent years, ammonia borane (AB) has attracted increasing attention as an efficient and safe storage medium for H 2 , [2][3][4][5][6] owing to the high capacity (19.6 wt % by weight and 0.145 kg L À1 by volume) and the stability in ambient atmosphere. [2,5] The practical application of AB as an on-board hydrogen medium is, however, limited by the sluggish dehydrogenation kinetics at 100 8C, [7][8][9] Other drawbacks of AB include the release of by-products and the lack of cost-effective methods for spent fuel regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported around 9 wt % hydrogen yield determined by TGA and volumetric quantification for the above mentioned Me-GBH. However, solid state NMR analysis of the residue after dehydrogenation still showed significant amounts of BH 4 À -species. Experiments employing Wilkinson's catalyst for the decomposition reaction showed considerable improvement in both reaction kinetics as well as overall efficiency.…”
mentioning
confidence: 98%